“Aplicación de cuatro dosis de fertilizante (micromate calcium fortified) a base de micro elementos en el cultivo de lechuga (lactuca sativa) variedad great lakes 659, bajo condiciones agroecológicas en la provincia de Lamas” - Jimenez Santos, Jose Estalin (2016)
This research was developed in the area of crops on the farm "PACIFIC", located in the province of San Martin Lamas region - Peru. lt was aimed to determine and evaluate the vegetativa characteristics and crop yield of · 1ettuce (Lactuca sativa) Lackes 659 Great variety, influenced by Granular fertilizar based on microelements; under agro-ecological conditions in the Province of Lamas. 5 treatments with Great variety Lackes 659, of which, with the application of T4 (100 kg ha-1 MCF) and T3 (75 kg ha-1 MCF) treatments the best yields were obtained with 2104 was used, 100.0 kg ha-1 and 100,687.5 kg ha-1 respectively, being statistically equal. With the application of 100 kg ha-1 Micromate Calciumm Fortified (T4) were the best agronomic traits in plant height (29.5 cm), number of leaves per plant (28.9 sheets) and plant weight (208.2 g) . With the application of 100 kg ha-1 Micromate Calciumm Fortified (T4) the highest value B I C was reached. With increasing applications Micromate Calciumm Fortified (independent variable) from 25 to 100 kg ha-1 and in relation to treatment TO (control), they described positive linear responses and relationships high correlation ( over 90%) over height plant, diameter of the stem, number of leaves per plant, plant weight and yield (dependent variables). Keywords: Fortified Calciumm Micromate, applications, applications, Great Lackes 659 performance.